Задорнов и К - Задорнов Михаил Николаевич (Эксмо, 2004)
Экземпляры: ф.6 (20161020) / Инвентарный номер: 1886 / Цена: / Сис.шифр: 84(2Рос=Рус)6-7 / Авт.знак: З-15 / ГРНТИ: 17.82.70 / ББК: 84(2Рос=Рус)6-7